Inhibitor-conjugated harmonic nanoparticles targeting fibroblast activation protein. Issue 54 (4th October 2019) - De Matos, Raphaël; Vuilleumier, Jérémy; Mas, Christophe; Constant, Samuel; Staedler, Davide; Gerber-Lemaire, Sandrine
Abstract : Harmonic nanoparticles, functionalized with a selective inhibitor of FAP, provide imaging probes targeting the fibroblastic element of the tumor stroma. Abstract : The recent progress in the engineering of nanosized inorganic materials presenting tailored physical properties and reactive surface for post-functionalization has opened promising avenues for the use of nanoparticles (NPs) in diagnosis and therapeutic intervention. Surface decoration of metal oxide NPs with ligands modulating circulation time, cellular uptake, affinity and extravasation through active targeting led to efficient cancer specific bioimaging probes. The most relevant cancer biomarkers studied so far include surface and transmembrane cancer cell receptors. More recently, tumor microenvironments and more specifically the fibroblastic element of the tumor stroma have emerged as a valuable target for diagnosis and treatment of several types of cancers. In this study, a low molecular weight ligand targeting fibroblast activation protein α (FAP), which is specifically expressed by activated fibroblasts of the tumor stroma, was synthesized. This ligand demonstrated nanomolar inhibition of FAP with high selectivity with respect to prolyl oligopeptidase (PREP) and dipeptidyl peptidase (DPP) IV, as well as good biocompatibility toward a human lung tissue model. Bismuth ferrite (BFO) harmonic nanoparticles (HNPs) conjugated to this ligand showed target-specific association to FAP as demonstrated by reverse ELISA-type assay using Human Fibroblast Activation Protein alpha/FAP Alexa Fluor® 594-conjugated Antibody and multiphoton multispectral microscopy experiments. These functionalized HNPs may provide new nanocarriers to explore the role of FAP in tumorigenesis and to target the fibroblastic component of the tumor microenvironment.